2022
DOI: 10.1097/olq.0000000000001605
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection With Chlamydial and Gonorrheal Infection Among US Adults With Early Syphilis

Abstract: Among 865 US adults with early syphilis, more than 1 in 4 had bacterial STI coinfection. This study supports routine mucosal screening for chlamydia and gonorrhea in people with syphilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Microbiology services and laboratories respond in many cases to requests for STI studies in which they do not know the clinical symptoms, so multiplex platforms that cover numerous possibilities are used, without being able in many cases to optimize the available resources. However, this strategy has brought as a benefit the diagnosis of coinfections, in clear increase in recent years [ 67 , 68 ].…”
Section: What Are the Problems Of Etiological Diagnosis Of Sti?mentioning
confidence: 99%
“…Microbiology services and laboratories respond in many cases to requests for STI studies in which they do not know the clinical symptoms, so multiplex platforms that cover numerous possibilities are used, without being able in many cases to optimize the available resources. However, this strategy has brought as a benefit the diagnosis of coinfections, in clear increase in recent years [ 67 , 68 ].…”
Section: What Are the Problems Of Etiological Diagnosis Of Sti?mentioning
confidence: 99%
“…Among sexually active, HIV-positive MSM, we previously have found high rates of C. trachomatis and/or N. gonorrhoeae coinfections in those with recent hepatitis C virus (HCV) infection (50%) and incident syphilis (36%) (4). A sub-study nested in a randomized controlled trial evaluating the treatment response of early syphilis also demonstrated a high rate of sexually transmitted coinfections (27%) in patients with early syphilis, including chlamydial infection, gonorrhea, and non-gonococcal urethritis (9). With the advances in polymerase-chain-reaction (PCR) technology, multiplex PCR assay can amplify several different DNA sequences simultaneously and enable rapid detection of sexually transmitted coinfections.…”
Section: Introductionmentioning
confidence: 97%